Are our healthcare workers well protected during COVID-19? Learning from current experiences and challenges / Siti Munira Yasin ... [et al.] - Yasin, Siti Munira; Muzaini, Kamarulzaman; Samsudin, Ely Zarina; Selamat, Mohamad Ikhsan; Ismail, Zaliha (Universiti Teknologi MARA Cawangan Selangor, 2020)
The outbreak of novel coronavirus disease 2019 (COVID-19) has been declared a Public Health Emergency of International Concern by the World Health Organization. The incidence of this pandemic continues to rise, with 40,665,438 confirmed cases and 1,121,843 deaths worldwide by 21 October 2020. During this public health crisis, healthcare workers are at the frontline of the COVID-19 outbreak response, and as such are at risk of being infected and developing job burnout while in the line of duty. This study reviews the history of COVID-19 outbreak, infection control measures in hospitals during COVID-19 outbreak, healthcare workers’ risk of infection and other health effects from battling COVID-19, and challenges and recommendations for protecting healthcare workers during this pandemic. At present, healthcare workers are every country’s most valuable resources, and their safety must thus be ensured. Strong medical leadership, clear pandemic planning, policies and protocols, continuous educational training, adequate provision of personal protective equipment, psychological support, and the provision of food, rest, and family support for healthcare workers would augment a climate of safety in the workplace, ensure their wellbeing, and improve their capacity to battle this ongoing pandemic.